Court Dispositions and Rearrest for Intimate Assault - Wooldredge, John (Crime & delinquency, 2005)
Researchers examining court dispositions and domestic violence recidivism have argued that disposition effectiveness varies by offender characteristics. We extended this research with analyses of 3,662 persons arrested for misdemeanor assaults on intimates in Hamilton County, Ohio. The incidence, prevalence, and time to rearrest are examined for arrestees with no filed charges, subsequently dropped charges, court-mandated treatment, probation, jail, and split sentences. No ,filed charges and probation correspond with significant differences in all outcomes across the entire sample. Moreover every disposition coincides with differences in rearrest for particular subgroups of arrestees (distinguished by violent histories, substance abuse, cohabitation, race, education, residential stability, and characteristics of neighborhood populations). [ABSTRACT FROM AUTHOR]